Anonymous birth between maternal autonomy and forced identity (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Maternal anonymity represents a phenomenon of disappearance from the life of the child. This paper addresses the several critical profiles arising from the balancing between the exercise of the right to anonymity and the right to know one’s origins and health data.
Keywords: Anonymous birth; Identity; Origins; Health data; Adoption